2004
DOI: 10.5194/bg-1-71-2004
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sources supporting benthic mineralization in mangrove and adjacent seagrass sediments (Gazi Bay, Kenya)

Abstract: Abstract. The origin of carbon substrates used by in situ sedimentary bacterial communities was investigated in an intertidal mangrove ecosystem and in adjacent seagrass beds in Gazi bay (Kenya) by δ 13 C analysis of bacteria-specific PLFA (phospholipid fatty acids) and bulk organic carbon. Export of mangrove-derived organic matter to the adjacent seagrasscovered bay was evident from sedimentary total organic carbon (TOC) and δ 13 C TOC data. PLFA δ 13 C data indicate that the substrate used by bacterial commu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 37 publications
3
16
2
Order By: Relevance
“…The higher percentage of bacterial biomarkers within the bay suggests a high bacterial biomass in the intertidal and seagrass bed sediments and water column. This is consistent with a previous study carried out in Gazi Bay using δ 13 C analysis of bacteriaspecific PLFAs (phospholipid fatty acids), which found that mangrove carbon was a significant source for bacteria mineralisation in the adjacent seagrass beds (Bouillon et al, 2004). Although branched FAs and 18 : 1 n7 are ascribed to both anaerobic and aerobic bacteria (Kaur et al, 2005;Meziane et al, 2006), the similar spatial patterns indicate similar response to the environmental conditions of Gazi Bay.…”
Section: Contribution Of Other Primary Producers To the Sediment And supporting
confidence: 91%
“…The higher percentage of bacterial biomarkers within the bay suggests a high bacterial biomass in the intertidal and seagrass bed sediments and water column. This is consistent with a previous study carried out in Gazi Bay using δ 13 C analysis of bacteriaspecific PLFAs (phospholipid fatty acids), which found that mangrove carbon was a significant source for bacteria mineralisation in the adjacent seagrass beds (Bouillon et al, 2004). Although branched FAs and 18 : 1 n7 are ascribed to both anaerobic and aerobic bacteria (Kaur et al, 2005;Meziane et al, 2006), the similar spatial patterns indicate similar response to the environmental conditions of Gazi Bay.…”
Section: Contribution Of Other Primary Producers To the Sediment And supporting
confidence: 91%
“…Fontugne and Duplessy, 1981), the DOC pool has δ 13 C values around −16 to −14‰, which is much more enriched than can be expected for marine phytoplankton. However, seagrasses which in our study site are found at the creek mouth and which cover large areas on the slope outside the system, are expected to have δ 13 C values within this range: although δ 13 C signatures for seagrasses were not determined in this particular system, other data from other sites along the east African coast range between −18.6 and −10.7‰ (Bouillon et al, 2004;Macia, 2004). The observed difference in marine end-member δ 13 C signatures and in the timing of local maxima during the tidal cycle results in an offset in δ 13 C signatures between the dissolved and particulate pools.…”
Section: Origin and Exchange Of Organic Mattermentioning
confidence: 77%
“…This had been demonstrated previously based on isotope data of bacterial markers (e.g. Bouillon et al, 2004), yet such data only referred to the upper layers of the sediments, where inputs of non-mangrove sources are likely to be most important (i.e. microphytobenthic production and deposition of suspended matter from the water column).…”
Section: Inorganic Carbon and Ch 4 Dynamicsmentioning
confidence: 90%
“…Due in large part to the productivity of these epiphytes, the primary productivity of seagrass beds is generally several times higher than that of adjacent unvegetated habitats (Moncreiff, Sullivan, & Daehnick, 1992). In addition, seagrass beds get carbon input from nearby coastal systems such as mangrove forests (e.g., Bouillon, Moens, & Dehairs, 2004). Several studies aimed to study the origin of carbon in these systems (e.g., Fleming, Lin, & Sternberg, 1990;Holmer & Bachmann Olsen, 2002;Marguillier, van der Velde, Dehairs, Hemminga, & Rajagopal, 1997) rather than to unravel the effects of total resource availability on consumers.…”
Section: Introductionmentioning
confidence: 99%